From spatial perception to referential meaning: convergent image schemas in the music of and texts about Beethoven’s piano sonatas - Antović, Mihailo; Jovanović, Vladimir Ž.; Popović, Mladen (Frontiers in Psychology, 2024)
This paper approaches the connection between musical constructs and visuo-haptic experience through the lens of the cognitive-linguistic notion of the “image schema”. The proposal is that the subconscious inference of spatial and haptic schematic constructs in music, such as vertical movement, will motivate their equally common occurrence in the language about that music, irrespective of the fact that this language never describes the musical structure in a one-to-one fashion. We have looked for five schemas in the scores for the first ten piano sonatas by Ludwig van Beethoven and three famous analytical and pedagogical texts about them: FORCE, indicating changes in musical dynamics and referential invocation of power-related terms in the books; PATH, identifying vertical movement in the music and suggestions of upward- or downward motion in the texts; LINK, suggesting the presence or absence of musical slurs and references to attachment or detachment in the language; BALANCE, indicating the loss and regain of consonance in the harmony and invocation of lost and recovered stability in the verbal semantics; and CONTAINMENT, allocating the nonharmonic tones that “belong” to their resolving notes in the scores and referring to physical or metaphorical enclosed areas in the texts. Results of the corpus analysis suggest the following conclusions: musical schemas outnumber linguistic ones sevenfold; moderate schema strengths are typical of both language and music; predominant valences are shared by language and music in three schemas out of five; hierarchies of five schemas by strength differ, though the strongest schemas are mostly shared. Yet the central finding is that the correlations between each schema pair for music and language, by scalarity and valence, are total. This implies that (1) schemas operate as semantic building blocks irrespective of the external “symbolical form” in which they are realized and (2) scalarized image schema complexes perceived in one cognitive mode may motivate the emergence of a corresponding number of the same complexes in another.